2019
DOI: 10.1523/jneurosci.3173-18.2019
|View full text |Cite
|
Sign up to set email alerts
|

The Divergent Roles of Dietary Saturated and Monounsaturated Fatty Acids on Nerve Function in Murine Models of Obesity

Abstract: Neuropathy is the most common complication of prediabetes and diabetes and presents as distal-to-proximal loss of peripheral nerve function in the lower extremities. Neuropathy progression and disease severity in prediabetes and diabetes correlates with dyslipidemia in man and murine models of disease. Dyslipidemia is characterized by elevated levels of circulating saturated fatty acids (SFAs) that associate with the progression of neuropathy. Increased intake of monounsaturated fatty acid (MUFA)-rich diets co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 83 publications
(118 reference statements)
1
47
0
Order By: Relevance
“…Next, we rendered these mice diabetic by the HFD model of obesity and prediabetes, a model extensively characterized in terms of PNS neuropathy progression and proven to be a useful tool for studying diabetes‐linked pathology and therapeutic interventions (Groover et al, 2013; O'Brien et al, 2018; O'Brien, Sakowski, & Feldman, 2014). Consistently with previous studies (Rumora et al, 2019; Saika, Kiguchi, Matsuzaki, Kobayashi, & Kishioka, 2019), 24 weeks after special feeding results in obesity, decreased NCVs and a neuropathic pain paradigm, validating presence of peripheral neuropathy in both mice strains. We (and others) did not observe any myelin ultrastructural abnormalities or peripheral axonal loss in WT mice fed with the HFD, challenging our understanding of why animals in this diabetic model develop sensory phenotypic abnormalities.…”
Section: Discussionsupporting
confidence: 91%
“…Next, we rendered these mice diabetic by the HFD model of obesity and prediabetes, a model extensively characterized in terms of PNS neuropathy progression and proven to be a useful tool for studying diabetes‐linked pathology and therapeutic interventions (Groover et al, 2013; O'Brien et al, 2018; O'Brien, Sakowski, & Feldman, 2014). Consistently with previous studies (Rumora et al, 2019; Saika, Kiguchi, Matsuzaki, Kobayashi, & Kishioka, 2019), 24 weeks after special feeding results in obesity, decreased NCVs and a neuropathic pain paradigm, validating presence of peripheral neuropathy in both mice strains. We (and others) did not observe any myelin ultrastructural abnormalities or peripheral axonal loss in WT mice fed with the HFD, challenging our understanding of why animals in this diabetic model develop sensory phenotypic abnormalities.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, the effects of HFDP and HFDS on adipose accumulation are profound, including elevated lipid levels, more lipid droplets, and larger droplet size. The HFD-induced elevation in TAG levels is an important marker for this collection of phenotypes, as high TAG levels are associated with disruption of lipid and glucose homeostasis, mitochondrial function, and other processes [ 33 , 34 ], all of which may contribute to metabolic disorders. Since the fatty acid composition is a key predictor of edible oil, we investigated the effects of both the soybean and palm oil in altering honey bee metabolism under HFD conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Another study reported increased sorbitol pathway activity with accumulation of glucose, sorbitol and fructose in the sciatic nerve due to HFD feeding in mice and demonstrated elevated oxidative-nitrosative stress in the sciatic nerve and DRG neurons [32]. The influence of specific dietary components such as saturated fatty acids have also been implicated in murine models of PN with demonstrable alterations in DRG mitochondrial function, ATP production and apoptosis [50,51]. Notably, the diet used here is rich in saturated fat, making these mechanisms highly relevant and worthy of further investigation.…”
Section: Discussionmentioning
confidence: 99%